COMPOSICION DE DIETA DE CNEMIDOPHORUS TIGRIS MARMORATUS (SAURIA: TEIIDAE) EN DUNAS DEL CENTRO DEL DESIERTO CHIHUAUHENSE - Gadsden E, Héctor; Palacios Orona, Luis (Instituto de Ecología, A.C., 2000)
In 1990 we studied the seasonal feeding patterns of the Western Marbied Whiptail (Cnemidophorus tigris marmoratus) in sand dunes of central Chihuahuan Desert, México (26° 50’ N, 103° 49' W). The stomachs of 35 males and 20 females were examined and the Importance valué (relative abundance + relativa volume + prey constancy), Shannon-Wiener diversity Índex and intersexual niche overlap (summer and autumn) of prey Ítems were determinad. Adult Isoptera were the most important prey during the three seasons studied (I.V. = 38.8 %, both sexes). Other important food Ítems were Lepidoptera (larvae), Dictyoptera (nymphs). Coleóptera (adults) and Araneae. This lizard showed an average H' = 1.1 and H'v = 2.7 and thus is considerad to have a generalist diet. The intersexual niche overlap was larga in summer and autumn (Ojk = 0.95). There were no differences in prey size between the sexes. The coefficient of variation for prey length (CV-PL) was larger in males, whereas it was smaller for snout-vent length (CV-SVL) in males. Males were significantly larger and heavier than females. The observad differences in body size between sexes might be relatad to differences in finite rate of annual survival among them.